The Ambiguities of Disciplinary Professionalization: The State and Cultural Dynamics of Canadian Inter-war Anthropology - Nurse, Andrew (Scientia Canadensis, 2007)
AbstractThe professionalization of Canadian anthropology in the first half of the twentieth century was tied closely to the matrix of the federal state, first though the Anthropology Division of the Geological Survey of Canada and then the National Museum. State anthropologists occupied an ambiguous professional status as both civil servants and anthropologists committed to the methodological and disciplinary imperatives of modern social science but bounded and guided by the operation of the civil service. Their position within the state served to both advance disciplinary development but also compromised disciplinary autonomy. To address the boundaries the state imposed on its support for anthropology, state anthropologists cultivated cultural, intellectual, and commercially-oriented networks that served to sustain new developments in their field, particularly in folklore. This essay examines these dynamics and suggests that anthropology's disciplinary development did not create a disjunctive between professionalized scholarship and civil society.